Improving the quality of point-of-care testing. (15th December 2017) - Price, Christopher P; Smith, Ian; Van den Bruel, Ann
Abstract: Background: It is suggested that new models of primary care should have better access to test results through the use of point-of-care testing (POCT). Objective: To determine whether quality management of POCT leads to better results. Methods: A comprehensive search of the literature on quality management of POCT in primary care, where the impact of participation in quality management programmes had been investigated with relevant outcome measures. Results: Three databases were systematically searched using key words relevant to POCT and quality management, covering from 1945 to January 2017. Titles and abstracts were reviewed for relevance and papers selected for review and data extraction. Five observational studies were found in which the performance of POCT for specific analytes in external quality assurance (EQA) programmes was used to assess improvement over a period of time, varying from 3.5 to 15 years. The tests monitored were HbA1c, urine albumin, C-reactive protein, glucose and haemoglobin. In each case, the performance of the test against defined analytical criteria was used to judge improvement in performance. Different summary performance criteria were used, including the imprecision of results over a period of time (two studies) and meeting defined target values for bias and imprecision of measurement (three studies). Performance improved with time and was associated with regular participation in EQA schemes and with the use of internal quality control (IQC) procedures. Conclusions: These findings indicate that adoption of quality management for POCT, including participation in IQC and EQA, with the support of laboratory medicine professionals, will improve the quality of the results 'produced'.